1999
DOI: 10.1097/00000433-199903000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Death Related to Midazolam Overdose During Endoscopic Retrograde Cholangiopancreatography

Abstract: We report a midazolam-related death that occurred during endoscopic retrograde cholangiopancreatography (ERCP). The acute intoxication due to midazolam overdose was confirmed by high-pressure liquid chromatography (HPLC) analysis of the blood samples taken from the patient in the intensive care unit (2.8 microg/ml) and postmortem (2.4 microg/ml). The case strongly emphasizes the necessity of the precautions that should be taken when midazolam is intravenously administered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…37 However, 4‐hydroxymidazolam is not detectable in human plasma following subtherapeutic midazolam doses,12 or detectable at sub‐ng/ml levels following therapeutic doses;25 in addition, the more important active metabolite 1‐hydroxymidazolam is always found in much lower plasma concentrations than midazolam 12,. 17 Thus, the described method may be usefully applied in cases of acute midazolam intoxication,38 within diagnostic procedures for brain death ascertainments,39–41 assays following fatal overdoses,6,, 24,, 42,, 43 or in cases of driving under the influence of drugs 44,. 45 In most of these applications, a negative or positive midazolam assay may help to screen samples with respect to further and possibly more complex chromatographic analyses.…”
Section: Resultsmentioning
confidence: 99%
“…37 However, 4‐hydroxymidazolam is not detectable in human plasma following subtherapeutic midazolam doses,12 or detectable at sub‐ng/ml levels following therapeutic doses;25 in addition, the more important active metabolite 1‐hydroxymidazolam is always found in much lower plasma concentrations than midazolam 12,. 17 Thus, the described method may be usefully applied in cases of acute midazolam intoxication,38 within diagnostic procedures for brain death ascertainments,39–41 assays following fatal overdoses,6,, 24,, 42,, 43 or in cases of driving under the influence of drugs 44,. 45 In most of these applications, a negative or positive midazolam assay may help to screen samples with respect to further and possibly more complex chromatographic analyses.…”
Section: Resultsmentioning
confidence: 99%
“…We found that midazolam was superior in alleviating pain or pain recollection during bone marrow biopsy, but its use is not without hazard. Deaths have been reported in other procedures after midazolam treatment, even in patients undergoing conscious sedation 19. In this study clinically important hypoxaemia was reversed by flumazenil in three patients (13%); the use of midazolam sedation requires the full precautions described by the Royal College of Anaesthetists to be taken.…”
Section: Discussionmentioning
confidence: 62%
“…Sedation-related adverse events occur in 6.5/1,000 endoscopic procedures [6] and may result from an overdose of the sedative agent [2,15]. Problems with sedation and aspiration contributed to the death of three patients in this series.…”
Section: Discussionmentioning
confidence: 99%
“…Perforation at upper GI endoscopy and pancreatitis subsequent to ERCP are well-recognized complications, particularly for therapeutic procedures [7,10,16,22]. However, delays in the endoscopy or in implementing therapy, aspiration pneumonia [16,20], oversedation [15,16], inexperience of the surgeon [16], and even performance of the wrong procedure remain rare, although potentially avoidable, adverse events.…”
Section: Discussionmentioning
confidence: 99%